A 60 Years Old Man with Adenocarcinoma of Colon and Lung with an Isolated Adrenal Metastasis: A Case Report - Sharma, Netay Kumer; Dey, Sankar Narayan; Rahman, Md Masudur; Islam, Mahzabeen; Mukthadira, -; Farzana, Mir Naz; Hasan, Rajibul (Community Based Medical Journal, 2021)
The incidence of synchronous colorectal and lung cancer associated with adrenal metastasis is relatively rare. We report of patient with tumour located in the right colic flexure adjoining ascending colon, mid and partly upper lobe of right lung. Pathological examination showed the colorectal and lung cancer were poorly differentiated adenocarcinoma. Right adrenal mass was adrenocortical metastatic carcinoma. Surgical treatment and postoperative adjuvant chemotherapy for the lung cancer were different from those for colorectal cancer with pulmonary metastasis. If possible, radical resection should be performed for each cancer when synchronicity is found. CBMJ 2020 January: Vol. 09 No. 01 P: 30-37